Ellsberg's 2-color experiment, bid-ask behavior and ambiguity - Mukerji, S; Tallon, J (University of Oxford, 2002)
Results in this note relate the observation of an interval of prices at which a DM strictly prefers to hold a zero position on an asset (termed 'bid-ask behavior') to the DM's perception of the underlying payoff relevant events as ambiguous, as the term is defined in Epstein and Zhang (2001). The connection between bid-ask behavior and ambiguity is established without invoking a parametric preference form, such as the Choquet expected utility or the max-min multiple priors model. This allows us to draw an observable distinction between bid-ask behavior that may arise purely due to first-order risk aversion type effects, such as those which could arise even if preferences were probabilistically sophisticated, and the bid-ask behavior that involve ambiguity perceptions.